2004
DOI: 10.1111/j.1464-410x.2003.04621.x
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal tunica albuginea plication to correct congenital and acquired penile curvature: a long‐term follow‐up

Abstract: Authors from Jerusalem evaluated the long‐term efficacy of a tunica albuginea dorsal plication technique in the treatment of congenital and acquired curvature of the penis. They assessed their experience in 83 patients aged 1‐8 years who underwent this procedure over a 10‐year period. They found it to be a simple technique with considerable long‐term efficacy. OBJECTIVE To evaluate the long‐term efficacy of a tunica albuginea dorsal plication technique for treating congenital and acquired penile curvature. PAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…Actually, our results are in contradiction with already published material, using absorbable sutures where younger patients (< 24 yr) had a higher chance of suture failure than elder patients (14). Long-term results of plication techniques in the pediatric setting are rarely reported, but success seems to be the rule (8,9,15,16). In our experience, the long-term degree of subjective satisfaction among patients with CPC was remarkable and supports the philosophy of corporoplasty in this setting.…”
Section: Commentscontrasting
confidence: 57%
See 1 more Smart Citation
“…Actually, our results are in contradiction with already published material, using absorbable sutures where younger patients (< 24 yr) had a higher chance of suture failure than elder patients (14). Long-term results of plication techniques in the pediatric setting are rarely reported, but success seems to be the rule (8,9,15,16). In our experience, the long-term degree of subjective satisfaction among patients with CPC was remarkable and supports the philosophy of corporoplasty in this setting.…”
Section: Commentscontrasting
confidence: 57%
“…In previous studies, satisfaction results were almost identical in both settings (16,20). In our experience, the differences affected all aspects including those related to the curvature correction, perhaps reflecting a better performance of plication techniques in the management of totally stable deformity, as in congenital curvatures; in other words, it might be that patients with PD presumed stable were still in progression.…”
Section: Commentsmentioning
confidence: 77%
“…As we have previously reported the formal Nesbit operation was performed in 4 and dorsal plication which was adopted since 1992 was required in the remaining 10 patients [10]. Corporoplasty fixed chordee in all but one patient who required additional dorsal plication and release of skin chordee 12 years following primary repair.…”
Section: Resultsmentioning
confidence: 99%
“…Theiss et al 11 showed that intercourse was possible in all study subjects following the correction. In a report by Chertin et al, 12 none of the 83 patients reported penile shortening or erectile dysfunction following surgery and there was no recurrence reported during median follow-up of 6 years. Following repair in another report, all patients showed elimination of penile curvature with preserved erectile function in 92% and an 83% full satisfaction rate.…”
Section: Congenital Penile Curvaturementioning
confidence: 99%